Analisis Kualitas Larutan Mol (Mikoorganisme Lokal) Berbasis Daun Gamal (Gliricidia Sepium) - IDA AYU YADNYA SENI; I WAYAN DANA ATMAJA; NI WAYAN SRI SUTARI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT Quality Analysis of MOL (Local Microorganism) Solution Based on Gamal (Gliricidia sepium) Leaves The purpose of this research was to find out the effects of gamal (Gliricidia sepium) leaves concentration and term of fermentation to the quality of MOL (local microorganism) solution. The research was held on September 2012 until November 2012, at Soil Laboratory, Faculty of Agriculture, Udayana University. Randomizing block design with two factors, including gamal leaves concentration (K) and fermentation term (F). The observation parameters of this research were total population of bacteria, total population of fungi, N-total, C-organic, C/N ratio. The analysis of gamal leaves concentration and the fermentation term was highly significant (P<0,01) affect. The total high population of bacteria in the K1 treatment be found the treatment F3 , 4,30 x 108 cfu ml-1, the total high population of bacteria in the K2 treatment can be found in the F3 treatment is 6,37 x 108 cfu ml-1, the total high of population of bacteria in the K3 treatment can be found in the F3 treatment is 8,63 x 108 cfu ml-1, the total population of bacteria in the K4 can be found in the F3 treatment is 9,07 x 108 cfu ml-1. The total population of fungi in the K1 treatment can be found in the F3 is 8,23 x 105 cfu ml-1, the total population of fungi in the K2 treatment can be found in the F3 is 8,27 x 105 cfu ml-1, the total population of fungi in the K3 treatment can be found in the F3 is treatment is 8,67 x 105 cfu ml-1, the total population of fungi in the K4 treatment can be found F3 treatment is 10,20 x 105 cfu ml-1. Concentration of 600 g/l gamal leaves on three weeks of fermentation have the best quality of mol solution. Keywords: Local Microorganisms (MOL), gamal leaves, fermentation term